Int. J. Adv. Res. Biol. Sci. 2018
DOI: 10.22192/ijarbs.2018.05.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and its Impact on the Elements of Soil and Plants in Helwan Area

Abstract: Over the past two decades, the threat of environmental pollution elements has attracted attention as much as the air pollution. Concentrations of many trace elements in the environment have been significantly affected by man's activities. The present study was made to evaluate the potential effects of ambient air pollutants (SO 2 , NO 2 , CO and PM10) on Calotropis procera and soil in Helwan city. The study also aimed to evaluate the damaging effect of human activities on soil and some plants, where samples wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…From our findings, the average bioavailability of PTEs declines in order as Zn > Cd > Cu > Pb > Ni > Co. Correspondingly, the general trends of the relative abundance of trace elements in vegetation studied previously in the area (El-Mekawy 2007 ) and (Alkhdhairi et al 2018 ), were Cd > Cu > Pb > Cr > Co and Zn > Pb > Cd > Cu respectively, supporting these findings.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…From our findings, the average bioavailability of PTEs declines in order as Zn > Cd > Cu > Pb > Ni > Co. Correspondingly, the general trends of the relative abundance of trace elements in vegetation studied previously in the area (El-Mekawy 2007 ) and (Alkhdhairi et al 2018 ), were Cd > Cu > Pb > Cr > Co and Zn > Pb > Cd > Cu respectively, supporting these findings.…”
Section: Resultssupporting
confidence: 89%
“…These portions of Pb, Cu, Cd and Zn under favourable conditions are available for wider food chain impact through plant uptake. Elevated concentrations of Cd, Zn, Pb and Cu recorded in some plant species collected from the study area by El-Mekawy 2007 , Galal et al 2016 and Alkhdhairi et al 2018 confirm the bio-accessibility and total bioavailability indicated by this result. The content of the exchangeable fraction (F1) is readily available for plant uptake.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Moreover, Cadmium and its compounds are categorized as Group 1 carcinogens for humans and the inhalation of high levels of Cd can produce severe damage to the lungs (Jaishankar et al, 2014, Satarug andMoore, 2004). Soils and crops in many region areas in Egypt are contaminated with heavy metals such as lead and cadmium due to air pollution emissions as the main source of heavy metals in Egyptian environment (Abdel-Latif, 2001, Abdel-Latif et al, 2013, Alkhdhairi et al, 2018, Salman et al, 2019. Other essential reasons for contamination of agricultural soils and crops in Egypt are lowquality irrigation water, pesticides, fertilizers, agricultural activities and municipal waste (El-Hassanin, 2020, Elnazer et al, 2015, Mahmoud and Ghoneim, 2016, Zeid et al, 2018.…”
Section: Introductionmentioning
confidence: 99%